STRIDE 위협 모델링에 기반한 클라우드 컴퓨팅의 쿠버네티스(Kubernetes)의 보안 요구사항에 관한 연구 - 이승욱(Seungwook Lee); 이재우(Jaewoo Lee) (한국정보통신학회논문지, 2022)
With the development of cloud computing technology, container technology that provides services based on a virtual environment is also developing. Container orchestration technology is a key element for cloud services, and it has become an important core technology for building, deploying, and testing large-scale containers with automation. Originally designed by Google and now managed by the Linux Foundation, Kubernetes is one of the container orchestrations and has become the de facto standard. However, despite the increasing use of Kubernetes in container orchestration, the number of incidents due to security vulnerabilities is also increasing. Therefore, in this paper, we study the vulnerabilities of Kubernetes and propose a security policy that can consider security from the initial development or design stage through threat analysis. In particular, we intend to present a specific security guide by classifying security threats by applying STRIDE threat modeling. 클라우드 컴퓨팅 기술의 발전으로 가상 환경을 기반으로 서비스를 제공하는 컨테이너 기술 또한 발전하고 있다. 컨테이너 오케스트레이션 기술은 클라우드 서비스를 위한 핵심적인 요소이며, 대규모로 구성된 컨테이너를 빌드, 배포, 테스트하는데 자동화로 관리하기 위한 중요한 핵심 기술이 되었다. 최초 구글에 의해 설계되었고, 현재 리눅스 재단에 의해 관리되고 있는 쿠버네티스는 컨테이너 오케스트레이션 중에 하나이며 사실상 표준으로 자리 매김을 하고 있다. 하지만 컨테이너 오케스트레이션 중 쿠버네티스의 사용이 증가하고 있음에도 불구하고, 보안 취약점에 의한 사고사례도 또한 증가하고 있다. 이에 본 논문에서는 쿠버네티스의 취약점을 연구하고, 위협 분석을 통해 개발 초기 또는 설계 단계에서부터 보안을 고려할 수 있는 보안 정책을 제안한다. 특히, STRIDE 위협 모델링을 적용하여 보안 위협을 분류함으로써 구체적인 보안 가이드를 제시하고자 한다.